2019
DOI: 10.31219/osf.io/wfcmx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The #nofilter Self: The Contest for Authenticity among Social Networking Sites, 2002–2016

Abstract: This study traces appeals to authenticity, over time, in the promotional material of leading social-networking sites (SNSs). Using the Internet Archive’s Wayback Machine, the public-facing websites of major SNS platforms—beginning with Friendster in 2002—were sampled at six-month intervals, with promotional language and visuals examined for authenticity claims. The authors tracked these appeals, with attention to changes in promotional copy, through to July 2016, among the most popular social media services (a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Researchers and online users widely understand "authenticity" to be a central organizing principle of social media, despite-or perhaps because of-the staggeringly uneven deployment of the concept across platforms, communities, and practices (e.g., Banet-Weiser, 2012; Duffy & Hund, 2015;Marwick, 2013;Salisbury & Pooley, 2017). Against this backdrop, our data revealed that platforms drew heavily upon the authenticity ideal in delineating legitimate and illegitimate practices of algorithmic optimization.…”
Section: Metaphors Of Authenticitymentioning
confidence: 79%
“…Researchers and online users widely understand "authenticity" to be a central organizing principle of social media, despite-or perhaps because of-the staggeringly uneven deployment of the concept across platforms, communities, and practices (e.g., Banet-Weiser, 2012; Duffy & Hund, 2015;Marwick, 2013;Salisbury & Pooley, 2017). Against this backdrop, our data revealed that platforms drew heavily upon the authenticity ideal in delineating legitimate and illegitimate practices of algorithmic optimization.…”
Section: Metaphors Of Authenticitymentioning
confidence: 79%
“…That's furious, somebody give this guy a Xanex" (Colbert, 2017). This resonates with Salisbury and Pooley's (2017) claim that social media users are "artifice detectives," looking for clues and cues of authenticity. Indexes provide us with evidence for Trump's authenticity, rather than symbolic claims.…”
Section: Indexical Versus Symbolic Authenticitymentioning
confidence: 57%
“…Politicians' appropriation of new technology for these ends has a long history (Horton & Wohl, 1956), and social media companies have gone to great lengths to market themselves as authentic expressive equipment. Salisbury and Pooley (2017) found that major social media platforms are "marinated with authenticity claims," such as a former Twitter CEO's remark that "authenticity is absolutely the key to a great tweet" (quoted in Kim, 2013). Social media's discourse of authenticity is based on the promise that their expressive apparatus-tweets, vlogs, selfies, and so on-allows users to construct an authentic self mediated through various texts.…”
Section: Political Authenticity and Texts Of The Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to users, platforms also play a role in defining their perceived categories; for example, while Instagram has often concentrated on highlighting its shopping experiences (Instagram, 2018), Snapchat has officially defined itself as a "camera company" (Snapchat, 2017). Moreover, platforms regularly compete for users by branding themselves in contrast to one another, often implying or suggesting that they offer a better social experience than their competitors (Salisbury & Pooley, 2017). Although a full discussion of potential categories linked to the four platforms is beyond the scope of this paper, it is clear all four are evolving in ways that complicate their top-level designations.…”
Section: Categorizing Facebook Twitter Instagram and Snapchatmentioning
confidence: 99%